Peran Strategis Taman Baca ‘Shekinah’ dalam Mendorong Perkembangan Kemampuan Belajar Anak di Kampung Kiarapayung, Kabupaten Bandung - Sitompul, Hesti; Aneke Aneke (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
This community service activity aims to improve the learning abilities of children in Sindanglaya Village, Cimeyan Sub-district, Bandung Regency, through non-formal education programs at Taman Baca Shekinah. The background of this activity is the low human resources and limited educational access in the local community. The activities carried out included learning assistance for elementary school students in grades 1–6, literacy classes for toddlers, and morning exercise for local residents. A descriptive qualitative method with a participatory approach was used. Data were collected through observation, interviews, and documentation. The results showed an increase in children’s learning abilities, active participation, and community involvement in supporting children's education. Formal school teachers acknowledged the acceleration in students' understanding of subject materials. This activity demonstrated that community reading parks play an important role in supporting formal education and building children's character in resource-limited areas. The implication of this program is expected to be a literacy empowerment model for similar communities in other regions.